ICASSP 2022 - 2022 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2022
DOI: 10.1109/icassp43922.2022.9746198
|View full text |Cite
|
Sign up to set email alerts
|

Towards Interpreting Deep Learning Models to Understand Loss of Speech Intelligibility in Speech Disorders Step 2: Contribution of the Emergence of Phonetic Traits

Abstract: Apart from the impressive performance it has achieved in several tasks, one of the most important factors remaining for the continuous progress of deep learning is the increased work related to interpretability, especially in a medical context. In a recent work, we presented competitive performance achieved with a CNN-based model trained on normal speech for the French phone classification and how it correlates well with different perceptual measures when exposed to disordered speech. This paper extends that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…To accomplish this, we calculated the Sørensen-Dice Index (SDI; Sørensen, 1948; Abderrazek et al, 2022), which is a similarity measure that takes into account both the shared elements and the size of the sets being compared to measure similarity between phoneme inventories of several language pairs. The SDI ranges from 0 to 1, where 0 indicates no similarity, and 1 indicates complete similarity.…”
Section: Linguistic Similarity Analysismentioning
confidence: 99%
“…To accomplish this, we calculated the Sørensen-Dice Index (SDI; Sørensen, 1948; Abderrazek et al, 2022), which is a similarity measure that takes into account both the shared elements and the size of the sets being compared to measure similarity between phoneme inventories of several language pairs. The SDI ranges from 0 to 1, where 0 indicates no similarity, and 1 indicates complete similarity.…”
Section: Linguistic Similarity Analysismentioning
confidence: 99%
“…In this section, we briefly describe the general analytic framework, Neuro-Concept Detector (NCD), proposed in [20]. This framework was designed for the interpretability of the deep rep-resentations of a DNN performing a classification task.…”
Section: The Ncd Frameworkmentioning
confidence: 99%
“…Conversely, if Sn,T x < −0.25, then the neuron n is considered as a detector of the opposite phonetic feature Tx, noted [-Tx]. Experiments conducted in [20] revealed interesting results. Indeed, it showed that interpretable neurons with phonetic feature encoding properties emerge in the fully connected layers of the CNN.…”
Section: The Ncd Frameworkmentioning
confidence: 99%
See 1 more Smart Citation